Green Investment Policy as Moderator of ESG and Profitability on Value Relevance in Indonesian Coal Firm - Rizaldi, Fredy; Arrozi, Muhammad Fachruddin (JASF: Journal of Accounting and Strategic Finance, 2025)
Purpose: This study investigates whether ESG disclosure and profitability affect the value relevance of accounting information proxied by Tobin’s Q in coal firms, analyse the Green Investment Policy (GIP) moderation role. It aims to show the ESG efforts and “green” capital allocation uncertainty into higher market valuation in an emission-intensive sector. Method: Archival coal companies analysis listed on the Indonesia Stock Exchange (IDX) for 2019–2024. Data collected from annual and sustainability reports. The empirical with panel data regression and moderated regression analysis (MRA) using interaction terms (ESG × GIP; Profitability × GIP), also robust standard errors in ensuring the inference in heteroskedasticity. Findings: ESG disclosure not statistically significant in influencing firm value, either directly or through interaction with Green Investment Policy (GIP). Meanwhile, the interaction between Profitability and GIP is positive and significant, indicating that profits connected to credible green investments are more favourable valued by the market. This suggest that investors prioritize the quality of profit deployment within a sustainable and verifiable framework, rather than merely the total amount of profits. In accounting terms, integrating profitability with credible green investment produces stronger value signals, reflected in higher Tobin’s Q. Novelty/Value: The study redefines value relevance by emphasizing the profits distribution for verifiable green investment than ESG disclosure alone. The study underlining mixed evidence on ESG with the financial performance grows to be value-relevant in relation with credible GIP. The results provide managers, investors, and policymakers to align financial and sustainability objectives in emission-intensive industries.